Bioassay-guided isolation of Triterpene compounds from Dillenia suffruticosa and their cytotoxic activities against cancer cells - Nurdin, Armania; Saiful Yazan, Latifah; Ismail, Intan Safinar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Previous studies showed the ability of Dillenia suffruticosa to inhibit the growth of cancer cells by means of cell cycle arrest and apoptosis, thus validating the traditional use of the plant in treating cancer. Therefore, the present study was designed to isolate and elucidate the bioactive compounds responsible for the anticancer properties of D. suffruticosa extract. Bioassay-guided fractionation of the most potent fractions of DCM and EtOAc extract of D. suffruticosa was performed via column chromatography followed by purification using preparative HPLC. The structures of the isolated compounds were elucidated by NMR spectroscopy. Biological experiment by MTT assay and a series of column chromatography resulted in the isolation of three triterpene compounds. However, only the structure of compound (3) was confirmed as 1-isopropenyl-4α, 4β, 8, 10, 14-pentamethyl-icosahydro-cyclopenta[a]chrysene-3, 17-diol. Another two compounds were labelled as (1) and (2), which currently are unidentified due to unsuccessfulness in the full analysis of the spectroscopic data that enable the assignment of all protons, carbons, and confirmation of the structure. Compound (2) isolated from DCM extract of D. suffruticosa was most cytotoxic towards the selected cancer cells compared to the other two compounds and selected chemotherapeutic drugs, tamoxifen, and cisplatin. The ability of the isolated compounds to inhibit the growth of cancer cells indicates that these compounds are the bioactive constituents in D. suffruticosa that is mainly responsible for the cytotoxic activities. For this reason, these isolated compounds could be used as a means for the standardisation of herbal product from D. suffruticosa.